2018
DOI: 10.1097/ta.0000000000001871
|View full text |Cite
|
Sign up to set email alerts
|

Shock volume: Patient-specific cumulative hypoperfusion predicts organ dysfunction in a prospective cohort of multiply injured patients

Abstract: Prognostic study, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
6
0
1
Order By: Relevance
“…Previously we demonstrated that MODS averaged from days two to five after injury, aMODS D2-D5 , identified patients at risk for prolonged ICU length of stay (ICU Days ), prolonged mechanical ventilation (MV Days ) and NI. [1,11,12] In this work, there was a stark threshold of aMODS D2-D5 > 4 that predicted poor outcomes.…”
Section: A C C E P T E Dmentioning
confidence: 69%
See 3 more Smart Citations
“…Previously we demonstrated that MODS averaged from days two to five after injury, aMODS D2-D5 , identified patients at risk for prolonged ICU length of stay (ICU Days ), prolonged mechanical ventilation (MV Days ) and NI. [1,11,12] In this work, there was a stark threshold of aMODS D2-D5 > 4 that predicted poor outcomes.…”
Section: A C C E P T E Dmentioning
confidence: 69%
“…[1,13] Previously, we demonstrated that cumulative hypoperfusion, measured by temporal integration of abnormally elevated shock index values over the first 24 hr after injury corresponded closely with transfusion requirements and organ dysfunction (Figure 2). [1,13] The cumulative hypoperfusion index, 24hr Shock Volume (24hr SHVL), demonstrated significantly greater correspondence with outcomes including organ dysfunction compared to Injury Severity Score (ISS) and Base Deficit (BD). Notably, organ dysfunction, nosocomial infections (NI) and transfusions increased abruptly in patients with 24hr…”
Section: Shock Tolerance and Shockmentioning
confidence: 80%
See 2 more Smart Citations
“…18 El índice de choque elevado es una herramienta clínica que tiene correlación positiva con marcadores de hipoperfusión, 5 se asocia a mortalidad 8 y discrimina a los pacientes con fiebre que pueden desarrollar sepsis. 19 Sin embargo, hasta donde sabemos, la asociación del índice de choque elevado con PDO no se ha evaluado lo suficiente, por lo que el objetivo principal de este estudio fue demostrar que el índice de choque > 0.70 lat/min/mmHg es un factor de riesgo de la PDO con un OR: 4.11 ( 20 en el que la evaluación seriada del índice de choque elevado demostró ser un factor de riesgo con un OR: 21.91 (5.77-83.25), sensibilidad: 90%, especificidad: 69% y área bajo la curva: 0.80 (0.72-0.88) para PDO. Un hallazgo importante fue que aquellos pacientes con PDO tuvieron índice de choque elevado que no disminuyó a un valor normal incluso hasta las 72 horas de evolución, mostrando que la evaluación dinámica del índice de choque tiene mayor utilidad clínica que sólo una medición, similar a lo referido por Maheshwari K y colaboradores, 21 quienes reportan que cada cuatro horas de exposición a un índice de choque elevado incrementó el riesgo de muerte 5.8% (4.6-7%) y de lesión renal aguda 4.3% (3.7-4.9%).…”
Section: Hallazgos Principalesunclassified